Significance of the Vedic Ethos and the Universality: A General Study - Nayana Goswami (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Vedic culture occupies an important role in the Indian tradition and Philosophy. The socio-religious heritage of Indian people is based on the Vedas, the oldest and sacred scripture of the entire world, which reflect the way of life, culture and Philosophy of ancient India. Indian has one of the richest civilisations of the ancient world. The word Veda means the great knowledge and the gems of Vedic Treasure-house should explore to reform the Indian Identity. Although it is not so easy task, but many Indologists both eastern and western have been done their scientific and significant works on the Vedic concepts of religion and philosophy, and their spiritual, moral, social and scientific value. So that, the theological hidden thoughts of the Vedas can be understood by the scholars and students of the Vedic or non-Vedic field of study. The human ethics and ideological value of ancient Indian Society is clearly observed in the Vedic age, which is Universally and traditionally rich. For the development of the human resource and its ethical value, we should have acquired the actual meaning of the Vedic thought. In this Research Paper, it has been focused to analyze the basic concept of the Universal value and ethos of Vedic literature in different directions of a society and its significance to the social reformation.